THE COGNITIVE FUNCTIONING OF SOCIALLY ISOLATED INDIVIDUALS MAY PROFIT FROM HIGH MENTAL WORK DEMANDS - Then, F. S.; Schroeter, M. L.; Witte, A. V.; Engel, Christoph; Löffler, Markus; Thiery, J.; Villringer, A.; Luck, Tobias; Riedel-Heller, Steffi Gerlinde (Elsevier BV, 2016)
Background: Previous studies have shown that individuals with poor social relationships have an increased risk for dementia. Dementia risk, however, can also be positively influenced by lifestyle factors such as high mental demands at work (in particular as the work environment affects a very long lifetime period). Thus, our objective was to investigate whether the cognitive functioning of socially isolated individuals may profit from high mental work demands. Methods: Analyses were based on n=10,000 participants (aged 40-80 years) of the population-based German LIFE-Adult-Study. All participants underwent medical examinations and filled out standardized questionnaires. Cognitive functioning was assessed via the Verbal Fluency Test (VFT) and the Trail-Making Test (TMT). Social relationships were assessed via the Lubben Social Network Scale (LSNS-6). Results: The difference in cognitive func- tioning between high and low mental work demand conditions was larger in socially isolated individuals (VFT: 2.7 words, TMT-B: 26 seconds) compared to socially well integrated individuals (VFT: 2.1 words, TMT-B: 9 seconds). Multivariate regression analyses – adjusted for age, gender, and education – indicated that both mental work demands as well as social relationships are significantly asso- ciated with the level of cognitive functioning